Use of allelopathic plant extract with herbicide - Ahmet Tansel SERİM; Nuran Pınar GÜZEL; İstem TÜRKTEMEL (Derim, 2015)
Herbicides are one of the plant protection products that have been discussed due to their adversely effects caused by the usage of them although they have an important role on the sustainability of crop production. Researches on the plant protection practices, such as the development of new herbicide application techniques, the reduction of the application rate, the use of adjuvant, changing herbicide application time and the use of allelopathic plant extract, and the applications based on the results of these research have increased in recent years. The cost of weed control may exceed the economic benefits because a large amount of plant extract is needed to control weeds alone with allelopathic chemicals. Using the mixture of plant extracts with the reduced rate of herbicides is important both to reduce environmental and economic losses and to prevent some problem caused by use of herbicide. The extracts of plants which have got allelopathic character, such as sunflower, sorghum, brassica and rice, are commonly used for this aim. The aim of presented review is to emphasize the efficacy of allelopathic plant extract with herbicide to control weeds and its economical contribution.